Randomized, Controlled Trial of Dexamethasone Versus Dexamethasone Plus Hydrocortisone as Prophylaxis for Hypersensitivity Reactions Due to Paclitaxel Treatment for Gynecologic Cancer. Issue 8 (1st October 2017) - Jeerakornpassawat, Dhammapoj; Suprasert, Prapaporn
Abstract : Objective: The aim of this study was to assess intravenous hydrocortisone (HCT) added to standard dexamethasone (DXM) prophylaxis for paclitaxel-associated hypersensitivity reactions (HSRs). Methods: Paclitaxel naives scheduled for 6 cycles of paclitaxel (plus platinum) were randomized to DXM alone (20 mg intravenously [IV]) versus DXM plus HCT (100 mg IV) as premedication including chlorpheniramine (10 mg IV), diphenhydramine (25 mg orally), and ranitidine (50 mg IV) 30 minutes before infusion. Clinic nurses observed for HSRs. Groups were well balanced for cancer type, stage, drug allergy, chemotherapy naivete, mean age, body mass index, and paclitaxel dose. Results: The 44 DXM controls underwent 213 cycles and the 42 investigational DXM plus HCT group 192 per protocol cycles. Hypersensitivity reactions were observed among 9 (4.2%) DXM only cycles compared with 1 (0.5%) among DXM plus HCT cycles ( P = 0.022). Hypersensitivity reactions occurred in 8 (18%) DXM only patients and in 1 (2.4%) among those correctly receiving DXM plus HCT ( P = 0.030). All HSRs occurred in cycles 1 to 3, within 10 to 40 minutes after infusion initiation, and peaked in cycle 2 (5/39) for DXM recipients and in cycle 3 (1/30) for DXM plus HCT. Hypersensitivity reaction severity was grade 1 in 3 DXM only recipients and grade 2 in 6 DXM and 1 DXM plus HCT. A sole grade 3 HSR was in an intention-to-treat DXM-HCT patient, who erroneously received no HCT. Hypersensitivity reaction symptoms were facial flushing (8 episodes), dyspnea (7), palmar rash (1), and transient hypotension (1). Paclitaxel infusion was suspended for treatment of HSRs; in all cases, symptoms mitigated and infusion successfully restarted for the remaining dose. Conclusions: Adding HCT to routine DXM prophylaxis significantly decreased paclitaxel HSR frequency.